Diffusion-Weighted Images Differentiate Benign From Malignant Thyroid Nodules - ALKAN, ALPAY; ERDEM, GÜLNUR; Erdem, Tamer; Karakas, Hakki Muammer; Mutlu, Deniz Yakar; Firat, Ahmet Kemal; ŞAHİN, İBRAHİM; Alkan, ALPAY (My University, 2010)
Purpose: To reveal the possible role of diffusion-weighted images (DWI) in the differential diagnosis of benign and malignant thyroid nodules by comparing the results of fine-needle aspiration cytology (FNAC).